1994
DOI: 10.1161/01.hyp.24.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II exerts differential actions on renal nerve activity and heart rate.

Abstract: Angiotensin II (Ang II) exerts complex actions on sympathetic nerve activity and heart rate, but these actions are incompletely understood. We performed three series of experiments in conscious rabbits to analyze the actions of exogenous and endogenous Ang II on renal sympathetic nerve activity and heart rate. (1) Graded intravenous doses of phenylephrine and Ang II suppressed renal sympathetic nerve activity to the same degree, whereas Ang II decreased heart rate much less than phenylephrine. (2) Ang II infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 33 publications
6
43
3
Order By: Relevance
“…In dogs, rabbits, and rats, systemic administration of ANG II has been demonstrated to increase blood pressure without causing the large reflex bradycardia that normally accompanies such increases in blood pressure suggesting that ANG II resets the baroreflex control of HR to a higher pressure (29,39). It is widely accepted that this effect of ANG II is due to central actions of this peptide on circumventricular organs such as area postrema (30,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dogs, rabbits, and rats, systemic administration of ANG II has been demonstrated to increase blood pressure without causing the large reflex bradycardia that normally accompanies such increases in blood pressure suggesting that ANG II resets the baroreflex control of HR to a higher pressure (29,39). It is widely accepted that this effect of ANG II is due to central actions of this peptide on circumventricular organs such as area postrema (30,34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its peripheral vasoconstrictor effects, this peptide has been known to modulate reflex regulation of HR and sympathetic activity through circumventricular organs such as the area postrema (13, 37). In rabbits, dogs, and rats, acute increases in circulating ANG II blunt baroreflex regulation of HR (1,31,38,39). It is interesting to know if centrally mediated effects of ANG II on baroreflex function are affected by differences in circulating estrogen levels and gender.…”
mentioning
confidence: 99%
“…9,23 In conscious rabbits, Kumagai and Reid 9 found that both an ACE inhibitor and an angiotensin type I receptor antagonist decreased arterial pressure and increased renal sympathetic nerve activity, whereas heart rate was unchanged. Thus, Ang II resets the baroreflex control of heart rate, leaving the control of renal nerve activity unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The aim of the present study was to assess the effect of short-term ACE inhibition on the adrenergic drive in patients with hypertension and renal artery stenosis. Given that animal experiments indicate different effects on renal nerve activity and heart rate in response to Ang II, 9 we also wanted to explore whether there is regional differentiation in the sympathetic response to ACE inhibition and nonspecific vasodilatation, with the latter used as a positive control test.…”
mentioning
confidence: 99%
“…Angiotensin II diminishes the sensitivity of this reflex by synaptically inhibiting it in the nucleus tractus solitarii, by increasing sympathetic nerve activity while decreasing the vagal tone to the heart. It also directly stimulates the myocardium, thus, shifting the operating 'set-point' for regulation of sympathetic outflow to higher BP (Isaacson & Reid, 1990;Kumagai & Reid, 1994;Averill, 2000;Averill & Diz, 2000;Bader et al, 2001;Balt et al, 2003;Diz et al, 2008;Smith et al, 2008;Hilzendeger et al, 2010;Arnold et al, 2011). This may explain the reductions in HR observed with the two highest doses of ang II given alone (figure 4.15).…”
Section: Does T Violacea Act By Blocking the Angiotensin II Receptors?mentioning
confidence: 98%